Development and Validation of an UHPLC-QqQ-MS Technique for Simultaneous Determination of Ten Bioactive Components in Fangji Huangqi Tang - Xiaoli Wang; Xiao Liu; Tingting Zhu; Baochang Cai (Journal of Analytical Methods in Chemistry)
The aim of this study is to develop an ultrahigh performance liquid chromatography method coupled with triple quadrupole mass spectrometry for simultaneous determination of tetrandrine, fangchinoline, atractylenolide I, atractylenolide III, calycosin-7-O-β-D-glucoside, glycyrrhizin, liquiritin, isoliquiritin, liquiritigenin, and isoliquiritigenin in Fangji Huangqi Tang (FHT). The chromatographic separation was performed on a reversed-C18 column, eluted with a mixture of 0.1% acetic acid and acetonitrile at 0.4 mL/min. The separation of these ten compounds was achieved by linear gradient elution. The method was strictly validated with respect to specificity, precision, accuracy, and repeatability. All the compounds showed good linearities (r≥0.999). The LOQs of the ten components were 0.36, 0.18, 0.09, 0.43, 0.02, 1.89, 0.26, 0.18, 0.61, and 0.48 ng/mL for tetrandrine, fangchinoline, atractylenolide I, atractylenolide III, calycosin-7-O-β-D-glucoside, glycyrrhizin, liquiritin, isoliquiritin, liquiritigenin, and isoliquiritigenin, respectively. The LODs of the ten components were 0.11, 0.05, 0.03, 0.13, 0.01, 0.57, 0.08, 0.05, 0.18, and 0.14 ng/mL for tetrandrine, fangchinoline, atractylenolide I, atractylenolide III, calycosin-7-O-β-D-glucoside, glycyrrhizin, liquiritin, isoliquiritin, liquiritigenin, and isoliquiritigenin, respectively. The method was proven to be specific and reliable, which would provide a meaningful basis for the quality control and evaluation of FHT during its clinical application.